Tracing Legal Regulations in Dealing with Cybercrime in Indonesia: Examining Obstacles and Solutions - Alief Tanding Pamungkas; Andi Muliyono; Nurjana Lahangatubun (Program Studi Hukum Pidana Islam IAIN Parepare, 2024)
The legal regulation of cybercrime in Indonesia faces several significant problems. Various aspects of life in the modern era, including the legal system, have been influenced by advances in information and communication technology. Cybercrime is increasing and becoming a serious threat that can disrupt social stability, state sovereignty, and public order. The purpose of this article is to explore the legal arrangements of cybercrime in Indonesia, analyze the problems, and provide solutions that can be implemented. This research uses a descriptive method, which allows to collect, analyze, and explain data related to cybercrime regulation in Indonesia. The results of the analysis show that the current legal arrangements still have several weaknesses, including limited human resources, inadequate facilities, and a limited budget. Consequently, the purpose of this study is to improve the understanding of cybercrime issues and offer more effective solutions in tackling them. Hopefully, the results of this study can help cybercrime law enforcement in Indonesia as well as strengthen international cooperation in efforts to prevent and counter cybercrime.